Mapping Potential Fishing Ground in Kuala Tungkal, Tanjung Jabung Barat, Jambi Province - Farhan Ramdhani; Septy Heltria; Suryono; M Hariski; Lauura Hermala Yunita; Sri Novianti; Yoppie Wulanda; Wulandari; Ester Restiana Endang Gelis (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service activity was carried out in Kuala Tungkal, Tanjung Jabung Barat Regency, Jambi Province, to address the challenges faced by fishermen in identifying potential fishing grounds. The primary focus was creating a map of potential fishing grounds based on oceanographic data to enhance the efficiency and productivity of fishermen. The methods included collecting oceanographic data, satellite imagery, and performing geospatial analysis using ArcGIS 10.8 software to predict and map the potential fishing grounds. Training sessions were held to teach fishermen how to use GPS and fishing ground maps, enabling them to predict and navigate fishing locations more effectively. This activity was carried out by involving several participations; fishermen, local government, and Fisheries Service of Tanjung Jabung Barat Regency. The map produced by the team depicts strategic locations in the waters of Kuala Tungkal (FMA 711) based on sea surface temperature (SST) and chlorophyll-a indicators. There are 105,633 potential fishing points being identified in this area. SST values range from 28.2°C to 32°C, and chlorophyll-a values range from 0.2 mg/m³ to 2 mg/m³.  The training outcomes demonstrated that most fishermen could effectively use GPS and the fishing ground map during fishing operations. The active participation of fishermen and the provision of technology training is pivotal in the program’s success. Consequently, the utilization of potential fishing ground maps based on oceanographic data has the potential to enhance fishermen's performance and contribute to sustainable fisheries resource management in the FMA 711 area.